The squat lobsters of the genus Sadayoshia Baba, 1969 (Crustacea: Decapoda: Anomura: Munididae): new records including six new species from the Pacific Ocean - Macpherson, Enrique; Baba, Keiji (Zootaxa, 2012)
Careful examination of the morphology of recently obtained specimens as well as previously reported specimens of thegenus Sadayoshia, initiated by unpublished molecular data that suggest the existence of several different species, led usto describe six new species. The species are very similar to one another and distinguished by very slight morphologicaldifferences. Some of the characters that were previously considered as intraspecifically variable in some species, proved to be valid for species discrimination. A dichotomous key to all species of the genus is provided.